PENGARUH MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DIKANTOR SATUAN POLISI PAMOMG PRAJA (SATPOL PP) KOTA BOGOR - Sunari; Christina Ekawati (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of motivation, discipline, and work environment on the performance of employees of the Bogor City Civil Service Police Unit (Satpol PP). The analysis method used was multiple linear regression with hypothesis testing through F test (simultaneous), t test (partial), and determination coefficient (R²). The results of the analysis showed that simultaneously the three independent variables had a significant effect on employee performance, as evidenced by the Fcal value of 96.416 > F-table 2.700 and the significance of 0.000 < 0.05. An Adjusted R Square value of 0.743 indicates that 74.3% of employee performance variations can be explained by motivation, discipline, and work environment, while the rest are influenced by other factors outside the model. Partially, motivation (tcal = 3.454; sig = 0.001) and work environment (tcal = 2.979; sig = 0.004) had a positive and significant effect on performance, while discipline (tcal = 1.646; sig = 0.103) showed no significant effect. The resulting regression equation is Y = 12.970 + 0.396X1 + 0.191X2 + 0.407X3. Of the three variables, motivation is the most dominant factor influencing employee performance, with the highest beta coefficient value of 0.385. These findings show the importance of increasing motivation and creating a conducive work environment in an effort to improve the performance of Bogor City Satpol PP personnel.